Finite sample correction factors for panel cointegration tests - Jaroslava Hlouskova; Martin Wagner (Institute for Advanced Studies (IHS), 2009)
In this paper we present finite T mean and variance correction factors and corresponding response surface regressions for the panel cointegration tests presented in Pedroni (1999, 2004), Westerlund (2005), Larsson et al. (2001), and Breitung (2005). For the single equation tests we consider up to 12 regressors and for the system tests vector autoregression dimensions up to 12 variables. All commonly used specifications for the deterministic components are considered. The sample sizes considered are T ϵ 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 200, 500.
Keywords: C12; C15; C23; 330; panel cointegration test; correction factor; response surface; simulation; Panel; Simulation; Kointegration; Schätztheorie